Climate Change and Variability: Farmers’ Perception, Experience and Adaptation Strategies in Makueni County, Kenya - Kitinya , Kirina T; Onwonga , Richard N.; Onyango , Cecilia; Mbuvi , Joseph P; Kironchi , Geoffrey (Asian Journal of Agriculture and Rural Development, 2012)
A better understanding of climate change and variability (CCV) from the farmer’s perspective is a key to prioritizing measures to address and prepare for its consequences. A survey involving 150 farmers was thus conducted in Makueni County, Kenya to document farmers’; perception, experience and adaptation strategies to CCV. About 86% of farmers perceived CCV as a major challenge with 53% indicating that significant changes in climate would manifest in 10-20 years. Significant changes in rainfall amounts and distribution had occurred over the years and were rated by 60% of farmers as the frequently experienced aspect of CCV. About 33% of farmers had heard of but not used decision support tools (DST) to inform their agricultural activities. Workshops and seminars were reported by 67% of farmers as principal sources of information on CCV. Additionally, 50% of farmers relied on traditional knowledge for weather prediction. Only 20% of farmers had alternative strategies; agroforestry and growing drought tolerant crops particularly sorghum and cowpea, to minimize effects of CCV. Another 67% of farmers prioritized; terracing, ridging and water harvesting as adaptation strategies to minimize negative effects of CCV. The farmers were thus aware of CCV and through experience, backed with traditional technical knowledge, had gained prerequisite skills for addressing its negative effects. Nevertheless farmers’ agricultural practices could be improved by use of forecasted weather data and application of DST. Consequently enhancing farmers’ preparedness to tackle challenges posed by CCV.